Brood Rearing and Dose Optimisation for Induced Breeding of Raikor, Cirrhinus reba (Hamilton, 1822) - David Rintu Das; Shamim Rayhan; Md. Rezoanul Haque; Nasima Begum; Mohammad Amzad Hossain; Debasish Pandit (Aquatic Sciences and Engineering)
An experiment on brood rearing and induced breeding of the near threatened fish species Raikor, Cirrhinus reba using the pituitary gland (PG), was conducted from March to August 2020 at the Floodplain Sub-station of Bangladesh Fisheries Research Institute, Santahar, Bogura. Broods were collected and reared in the ponds of the hatchery complex. The total length (cm), body weight (g), gonad weight (g), and gonado-somatic index (%) of this species were measured during the rearing period. To standardize the breeding technique, a total of 90 brood fish of C. reba were treated with different doses of PG, specifically, 2.0, 4.0, 6.0 mg/kg body weight for females and 1.0, 2.0, 3.0 mg/ kg body weight for males in different treatments, namely T1, T2, and T3 respectively. A significant difference (p<0.05) was observed in fecundity, ovulation (%), and the fertilization rate (%) among the treatments. Based on the results, T2 (4.0 mg/kg body weight for females, 2.0 mg/kg body weight for males) produced the most favorable results. The current observations could be applied to C. reba stimulated breeding for the advancement of hatchery formation. More research on the nursing, nurturing, and culture of the near- threatened C. reba at varied densities and feedings is necessary for their conservation and restoration.